Effects of gender and years of working experience on primary school teachers' health assessment behaviour in Ibadan south west local government area, Oyo State (2020)
The average Nigerian children spend at least seven to nine hours a day and five days in a week in schools where they face significant health challenges resulting from daily activities and risk-taking behaviour which may adversely affect their health and ability to learn. Previous studies revealed poor personal hygiene practices among public primary school pupils. This study, examined the effects of gender and years of working experience on primary school teachers' health assessment behaviour in Ibadan South West Local Government Area of Oyo State. The study adopted non-equivalent pre-test -post-test control quasi experimental design using 2x2x2 factorial matrix. One hundred and eighty teachers selected through multistage sampling procedure from sixty-five public primary schools in the study area were randomly assigned to experimental group and control group. A structured Teachers' Health Assessment Behaviour Questionnaire (THABQ), and a self-structured Pupil Health Assessment form were used to collect information from the participants was adapted, a reliability coefficient of .76 was obtained using cronbach alpha. Study lasted for eight (8) weeks. Analysis of covariance (ANCOVA) was used to test the hypotheses at 0.05 alpha level. 107(59.4%) primary school teachers had no time for health assessment of their pupils. Findings showed that there was no significant main effect of gender on primary school teachers' health assessment behaviour in Oyo State (F (2,177) = 3.360, p>.05, ƞ(2) =.019). There was a significant main effect of work experience on primary school teachers' health assessment behaviour in Oyo state (F(2,177) = 31.022, p<.05, ƞ(2) = 149). Interaction effects of work experience and gender was significant on Primary school teachers' health assessment behaviour (F(1,175) = 17.227, p<.05, ƞ(2) =.003). It was recommended that there is need for regular advocacies for improvement and sustainable health assessment behaviour among primary school teachers in Ibadan South West Local Government Area.